RANCANGAN INSTRUMEN UJI KOMPETENSI LITERASI SAINS PENGETAHUAN BIOLOGI BAGI SISWA SMA DI RIAU - Aisyah Zumira; Mariani Natalina L; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to determine the quality of scientific literacy competency test on biology knowledge instrument. This research is a development research using ADDIE model with stages which are analyzed, design, and development. During the process, this research is divided into two stages, namely research and development. The research phase includes needs analysis, design, and instrument development. The development stage includes validation to obtain validity by validator, first trial, and second trial. The subjects in this study is the questions of scientific literacy that has been tested in PISA 2006. Instruments used to collect data are validation sheet and scientific literacy competence test questions that have been designed. Validation is done to see the validity of competence test instrument of scientific literacy that is developed, while the test result aims to know the quality of the realibility, difficulty level, distinguishing power, and distractor function. The result of the research shows that the scientific literacy competency test on biology knowledge designed has already qualified with valid category. This instrument then can be used as a training material for senior high school students, especially in Riau Province, to improve their scientific literacy skills.Key Words: Design, instrument, scientific literacy